Formation pathways, stability and chemical characteristics of soil aggregates in agroecological management systems - Rossi, Celeste Queiroz; Pereira, Marcos Gervasio; Moura, Octávio Vioratti Telles de; Almeida, Anástacia Perci Campos de (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to identify the formation pathways of biogenic, intermediate, and physiogenic aggregates, as well as their stability and chemical characteristics in different agroecological management systems. Five areas were chosen for sampling in Argissolo Vermelho-Amarelo (Ultisol), in the municipality of Seropédica, in the state of Rio de Janeiro, Brazil: SAF, 10-year agroforestry system; C-SOL, 15-year full-sun coffee; C-SOM, 15-year shaded coffee; AL-FLE, 10-year alleys with flemingia (Flemingia macrophylla); and PD, 6-year no-tillage system with corn and eggplant. Soil samples were collected at the 0.00–0.05 and 0.05–0.10-m soil depths, and the fraction retained in sieves of 9.7 and 8.0 mm were used to identify the different types of aggregates. After separation, the stability and chemical characteristics of each aggregate type were evaluated. The proportion between the aggregate types was not affected by the managements systems, and the relative contribution of intermediate aggregates to the total aggregate mass was higher than that of the other ones. The C-SOL and C-SOM systems show the highest total organic carbon, organic carbon associated with minerals, and particulate organic carbon, irrespectively of the evaluated systems and depths.